Human Immunodeficiency Virus Type 1 and tuberculosis co-infection in multinational resource limited settings: increased neurological dysfunction (2019)
Background. AIDS Clinical Trial Group 5199 compared neurological and neuropsychological test performance of human immunodeficiency virus type 1 (HIV-1)–infected participants in resource-limited settings treated with 3 World Health Organization–recommended antiretroviral (ART) regimens. We investigated the impact of tuberculosis (TB) on neurological and neuropsychological outcomes. Methods. Standardized neurological and neuropsychological examinations were administered every 24 weeks. Generalized estimating equation models assessed the association between TB and neurological/neuropsychological performance. Results. Characteristics of the 860 participants at baseline were as follows: 53% female, 49% African; median age, 34 years; CD4 count, 173 cells/μL; and plasma HIV-1 RNA, 5.0 log copies/mL. At baseline, there were 36 cases of pulmonary, 9 cases of extrapulmonary, and 1 case of central nervous system (CNS) TB. Over the 192 weeks of follow-up, there were 55 observations of pulmonary TB in 52 persons, 26 observations of extrapulmonary TB in 25 persons, and 3 observations of CNS TB in 2 persons. Prevalence of TB decreased with ART initiation and follow-up. Those with TB coinfection had significantly poorer performance on grooved pegboard (P < .001) and finger tapping nondominant hand (P < .01). TB was associated with diffuse CNS disease (P < .05). Furthermore, those with TB had 9.27 times (P < .001) higher odds of reporting decreased quality of life, and had 8.02 times (P = .0005) higher odds of loss of productivity. Conclusions. TB coinfection was associated with poorer neuropsychological functioning, particularly the fine motor skills, and had a substantial impact on functional ability and quality of life.